Biofortification of tomato with stabilized alkaline silicate and silicic acid, nanosilica, and potassium silicate via leaf increased ascorbic acid content and fruit firmness - dos Santos, Márcia Masson Mendes [UNESP]; da Silva, Gilmara Pereira [UNESP]; Prado, Renato de Mello [UNESP]; Pinsetta Junior, José Sidnaldo [UNESP]; Mattiuz, Ben-Hur [UNESP]; Braun, Heder (Taylor & Francis, 2022)
Leaf spraying of silicon (Si) depending on the source and concentration can biofortify the tomato fruit by increasing the content of ascorbic acid and the firmness of the fruit. The objective of this study was to determine whether foliar spraying of Si from different sources and at several concentrations provided Si biofortified tomatoes and to evaluate their technological quality. The experiment was carried out in a greenhouse in a pot. The treatments consisted of four Si sources (monosilicic acid, potassium silicate, potassium silicate and sodium silicate mixture, and nanosilica) and four Si concentrations (0.0, 0.2, 0.4 and 0.6 g L−1) arranged in randomized blocks with five replicates. After flowering, the Micro-Tom tomato plants were sprayed with Si once a week for five weeks. Si applied via foliar in the reproductive phase of tomato plants is efficient for providing Si biofortified tomato while the concentration of 0.4 g L−1 Si from the monosilicic acid source resulted in the highest increase of ascorbic acid, titratable acidity, and fruit firmness.
Keywords: fruit quality; silicon concentrations; Solanum lycopersicum